2022
DOI: 10.3329/bjsir.v57i4.62651
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, thrombolytic, cytotoxic and antibacterial activities of leaves of Vitex peduncularis

Abstract: Vitex peduncularis (Verbenaceae), a perennial tree, is locally utilized for possessing multifaceted pharmacological properties including analgesic, antimalarial, anti-angina, antidiabetic, antioxidant, anti-inflammatory and hepatoprotective. Hence, this study aims to evaluate their antioxidant, thrombolytic, cytotoxic and antibacterial activities from the methanolic crude extract and its various solvent fractions. Data from antioxidant and thrombolytic assay displayed that Kupchan partitioned chloroform solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It just needs a tiny amount of test material, which is affordable and does not require aseptic methods. This bioassay evaluates cytotoxicity, antibacterial activities, pesticidal effects, and various pharmacologic actions [24]. The findings of this study suggest that chemicals with biological activity, such as those that inhibit enzymes and interfere with ion channels, are found in the bark extracts of X. mekongensis and endophytes.…”
Section: Discussionmentioning
confidence: 88%
“…It just needs a tiny amount of test material, which is affordable and does not require aseptic methods. This bioassay evaluates cytotoxicity, antibacterial activities, pesticidal effects, and various pharmacologic actions [24]. The findings of this study suggest that chemicals with biological activity, such as those that inhibit enzymes and interfere with ion channels, are found in the bark extracts of X. mekongensis and endophytes.…”
Section: Discussionmentioning
confidence: 88%
“…An enlarged calyx encloses fruit, and seeds are exalbuminous [21] . The species has numerous vernacular or regional names, e.g., Chang Xu Jing in China, Korobaong in Bengali, Horina in Chittagong [24] , Charaiygorwa in Hindi ('charai' means bird and 'gorwa' means leg) [25] and Goda in Bangladesh [21,26] . The hardcoated seed of V. peduncularis is naturally propagated from the seed despite having a very low natural germination rate.…”
Section: ~ 120 ~mentioning
confidence: 99%
“…[10] . Bark on stems and leaves both have antifungal, antibacterial, antioxidant, antidepressant [56] , insecticidal effects [10] , larvicidal efficacy against A. stephe and C. quinquefasciatus [57, 58,] , thrombolytic and cytotoxic properties [26] . Kirtikar and Basu [59] reported that in Chota Nagpur regions, localities use its bark to address aches and pains.…”
Section: Conventional Applicationsmentioning
confidence: 99%